Model for Plasmid Evolution Mediated by site-specific recombination at oriT and Xer sites - Tran, Tung (2012)
Plasmids pPAB19-1, pPAB19-2, pPAB19-3, and pPAB19-4, isolated from Salmonella and Escherichia coli clinical strains from hospitals in Argentina, were completely sequenced. These plasmids include the qnrB19 gene and are 2,699, 3,082, 2,989, and 2,702 nucleotides long, respectively, and they share extensive homology among themselves and with other previously described small qnrB19-harboring plasmids. The genetic environment of qnrB19 in all four plasmids is identical to that in these other plasmids and in transposons such as Tn2012, Tn5387, and Tn5387-like. Nucleotide sequence comparisons among these and previously described plasmids showed a variable region characterized by being flanked by an oriT locus and a Xer recombination site. We propose that this arrangement could play a role in the evolution of plasmids and present a model for DNA swapping between plasmid molecules mediated by site-specific recombination events at oriT and a Xer target site.